Has the Grexit news affected euro area financial markets? - Wildmer Gregori; Agnese Sacchi (Publications Office of the European Union, 2017)
This paper investigates whether rumours about Greek exit from the euro area have spilled over into other European countries' sovereign bond yields. Our empirical analysis is based on more than 64,000 daily news items on Grexit between December 2014 and October 2015. We build a Grexit intensity index based on the daily change of Grexit news items to capture policy uncertainty about the euro area break-up. Our results suggest that higher intensity of Grexit news drives up government bond yields in peripheral countries (Italy, Portugal, and Spain, excluding Ireland), but that there are no effects on core countries. The asymmetric reaction to Grexit news seems to support a more general `market-based fiscal disciplining' mechanism at work in monetary unions.
Keywords: E43; E62; G12; G14; 330; Grexit; financial markets; government bond; news; euro area; GARCH